Long Memory in the Indonesia Stock Exchange - Panggabean, Martin P. H. (The Indonesian Capital Market Review, 2018)
The aim of this study is to investigate the existence of long-memory process in the Indonesia stock market. This study provides two major contributions and one anomaly. First, this is the first study on long-memory conducted on the Indonesia Stock Exchange at individual stocks. Second, this study uses the method of Detrended Fluctuation Analysis (DFA), supplemented by empirical confidence interval introduced by Weron (2002) and Kristoufek (2010). Our analysis uncover an anomaly that three out of thirteen of the most liquid shares in the Indonesia Stock Exchange exhibit mild long memory process in the daily return data. This result, however, is not robust to length of series utilized. All thirteen stocks exhibit long memory process in the absolute daily return which represent risk.